THE SIGNIFICANCE OF RURAL SERVICE CENTRES IN DRIVING DEVELOPMENT IN AHOADA WEST, RIVERS STATE, NIGERIA - Okwudili , Nwankwo Chijioke (Ayden Journal of Management and Social Sciences, 2024)
This study examined potential rural service centres as engines for rural development in Ahoada West Local Government Area. Three objectives, three research questions and one hypothesis guided the study. The descriptive survey research design was adopted. Through the use of purposive sampling technique, a structured questionnaire was used to collect data from 400 respondents from twenty (20) selected potential service centres (communities) in the area. The data collected were analyzed using descriptive statistics and Shimbel Accessibility Index for the research questions, while the hypothesis was tested using z-test statistic. The findings revealed that Akinima, Akaramini, Idul, Mbiana, Okogbe, Ukperede, Oshi, Emezie, Oyakama, Oshika, Okaki and Ubeta are the potential settlements that need to be developed to the status of full rural service centres. These potential rural service centres can contribute to rural development to a very high extent. However, intra-communal conflict, theft, insecurity (youth restiveness, militancy, kidnapping), bad roads, and poor electricity supply are the current challenges in these potential rural service centres. The study recommended that government should help to provide basic infrastructures, tighten security, etc. so as to enable these service centres transmit development impulses to the surrounding villages and hamlets in the area.